Methods of teaching English language: A Case of Junior High Schools in West Akim Municipality - Ofosua, Grace; Akpanglo-Nartey, Rebecca Atchoi (International Journal of Rehabilitation and Special Education (IJRSE), 2024)
This study sought to investigate the dominant method employed by English teachers at the Junior High School level in West Akim Municipality and its impact on students’ writing performance in English language. The study used a mixed-methods approach with questionnaires, interviews, and observation to obtain data from 20 teachers and 251 students, who were randomly sampled as respondents. The results revealed that most of the teachers used the Grammar Translation Method which impacted negatively on the students’ writing performance. It is therefore recommended that English teachers adopt the Eclectic Approach as there is no single optimal method for every teaching method, and integrating different teaching methods complements each other.